Efficacy and safety of a multiherbal formula with vitamin C and zinc (Immumax) in the management of the common cold - Mostafa Yakoot; Amel Salem (International Journal of General Medicine, 2011)
Mostafa Yakoot1, Amel Salem21Green Clinic, Alexandria, Egypt; 2Mabbarah Hospital, Alexandria, EgyptObjective: To study the potential efficacy and tolerability of a natural multiherbal formula (Immumax) containing Echinacea extract 120 mg, garlic powder 100 mg, Nigella sativa oil 200 mg, and Panax ginseng extract 50 mg plus vitamin C 50 mg and elemental zinc 7.5 mg in the treatment of patients suffering from the common cold.Design and setting: The study was conducted in a prospective, double-blind, randomized, controlled study design in an outpatient setting.Patients and methods: Sixty-two eligible patients with symptoms of the common cold were randomized to either Immumax or placebo treatment groups for the duration of their symptoms or a maximum of 14 days. Resolution rates were estimated using Kaplan–Meier analysis, and resolution profiles were compared between groups using the log-rank test. The mean percentage change in total symptom severity scores at days 4 and 8 from baseline were compared between the two groups by one-way analysis of variance (ANOVA).Results: The median (interquartile range) time to resolution of all symptoms was 8 (5–9) days in the placebo group and 4 (3–6) days in the Immumax group. The results of the log-rank test indicate that symptoms resolved significantly faster in the Immumax group than in the placebo group (P < 0.001). The mean percentage reduction in total symptom severity scores from baseline at days 4 and 8 was significantly greater in the Immumax group than in the placebo group by one-way ANOVA (P < 0.01).Conclusion: We can conclude from our study that Immumax is helpful in reducing the duration and severity of common cold symptoms.Keywords: Immumax, common cold, multiherbal